Online education in a hurry: Delivering pediatric graduate medical education during COVID-19. (March 2021) - Teele, Sarah A.; Sindelar, Anthony; Brown, David; Kane, David A.; Thatte, Nikhil; Williams, Ryan J.; Gueverra, Joy; Wolbrink, Traci A.
Abstract: In the setting of the coronavirus disease 2019 (COVID-19) pandemic, an emergency hospital-wide eWork policy was enacted at Boston Children's Hospital on March 16, 2020. The number of clinicians on campus was restricted to only essential personnel, guidelines limited clinical care delivery to solely non-elective patients, and strict maximums were placed on the numbers of people allowed to congregate in the same physical space. With this abrupt transition to social distancing and electronic communication, the established approach to educating graduate medical trainees became obsolete overnight. Anticipating significant impact on trainee and faculty professional and personal lives, the importance of adaptive teaching strategies was evident. This document details one approach to redesigning the clinical learning system including a description of the learners and environment, the pedagogical principles that guided the approach, and technological tools used in implementation. Additionally, available literature pertinent to this topic is explored, assessment of the work to date is presented, and suggestions are provided regarding future directions related to online graduate medical education. Highlights: Online graduate medical education is complementary to traditional approaches. Opportunities for innovation in graduate medical education Blended teaching may play a prominent role in the future of medical education. Collaboration is critical for optimizing learning opportunities.